Lithium-supplemented composite material, preparation method thereof, positive electrode material, and secondary battery
By coating anionic surfactant on the lithium supplement material, the problem of residual alkali generation in the existing positive electrode lithium supplement additive is solved, and the first charging efficiency and overall electrochemical performance of the battery are improved.
Patent Information
- Application Number
- CN202210882232.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-07-26
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2042-07-26
AI Technical Summary
The existing cathode lithium supplement additive materials contain more residual lithium sources, resulting in the generation of residual alkali, affecting the quality of the cathode sheet, and aggravating the decline in battery performance under high temperature conditions.
A lithium supplement composite material is used, which includes a lithium supplement material and a cladding layer coated on the surface of the lithium supplement material, and the cladding layer contains anionic surfactant. By preparing a solution containing anionic surfactant, lithium supplement material is added to the solution for mixing and drying, a lithium supplement composite material is obtained.
Effectively prevent the generation of residual alkali, reduce the residual alkali value of lithium supplement material, improve the coating uniformity of the positive electrode slurry and the quality of the positive electrode sheet, and improve the first charging efficiency and overall electrochemical performance of the battery.
Smart Images

Figure CN115347162B_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of electrode active materials, and in particular relates to a lithium-supplementing composite material and a preparation method thereof, a positive electrode material, and a secondary battery. Background Art
[0002] Adding a small amount of positive electrode lithium supplement additives to the positive electrode slurry is an effective method for replenishing lithium in lithium-ion batteries. However, the existing positive electrode lithium supplement additive materials contain a large amount of residual lithium sources, which will react with water and carbon dioxide in the air to generate residual alkali. In the preparation process of the positive electrode slurry, these residual alkalis will react with the binder, and chemical gelation is prone to occur during the stirring process of the positive electrode slurry, thereby affecting the quality of the positive electrode sheet. In addition, under high temperature conditions, the residual alkali will also react with the electrolyte solution to generate gas or solid matter, increase the gas production or impedance of the battery, and cause a decrease in battery performance.
[0003] Therefore, how to develop a lithium-supplementing material that can effectively prevent the generation and dissolution of residual alkali is an urgent problem to be solved. Summary of the invention
[0004] The purpose of the present application is to provide a lithium-supplementing composite material and a preparation method thereof, a positive electrode material, and a secondary battery, aiming to solve the problem that the existing positive electrode lithium-supplementing additives easily generate residual alkali, resulting in a decrease in the electrochemical performance of the battery.
[0005] In order to achieve the above application purpose, the technical solution adopted in this application is as follows:
[0006] In a first aspect, the present application provides a lithium-supplementing composite material, comprising a lithium-supplementing material and a coating layer coated on the surface of the lithium-supplementing material, wherein the coating layer contains an anionic surfactant.
[0007] In a second aspect, the present application provides a method for preparing a lithium-supplemented composite material, comprising the following steps:
[0008] preparing a solution containing anionic surfactant;
[0009] The lithium supplement material is added into a solution containing an anionic surfactant for mixing, and then dried to obtain a lithium supplement composite material.
[0010] In a third aspect, the present application provides a positive electrode material, which contains the lithium-supplementing composite material provided by the present application or the lithium-supplementing composite material prepared by the preparation method of the lithium-supplementing composite material provided by the present application.
[0011] In a fourth aspect, the present application provides a secondary battery, which contains the positive electrode material provided by the present application.
[0012] Compared with the prior art, this application has the following beneficial effects:
[0013] The lithium-supplementing composite material provided in the first aspect of the present application comprises a lithium-supplementing material and a coating layer coated on the surface of the lithium-supplementing material, the coating layer contains an anionic surfactant, and the lithium-supplementing material contained therein can be used for lithium-supplementing. When the battery is in the first cycle of charging, the lithium-supplementing material can replenish the lithium ions consumed by the formation of the SEI film at the negative electrode, so that the lithium ions in the battery system remain abundant, thereby improving the battery's first charging efficiency and overall electrochemical performance. The anionic surfactant coating layer contained therein effectively prevents the generation of residual alkali, can reduce the residual alkali value of the lithium-supplementing material, can alleviate the damage of the residual alkali to the binder in the positive electrode slurry, and reduce the viscosity of the positive electrode slurry, thereby achieving uniform coating and improving the quality of the positive electrode sheet. In addition, the anionic surfactant is tightly attached to the surface of the lithium-supplementing material, which can increase the stability of the material structure, prevent the lithium-supplementing material from agglomerating, and is conducive to giving full play to the lithium-supplementing effect of the lithium-supplementing material, thereby further improving the battery's first charging efficiency and overall electrochemical performance.
[0014] The second aspect of the present application provides a method for preparing a lithium-supplementing composite material, which comprises first preparing a solution containing an anionic surfactant; then adding the lithium-supplementing material to the solution containing the anionic surfactant for mixing, and then drying to obtain the lithium-supplementing composite material. The present application uses an anionic surfactant to coat the lithium-supplementing material, which is conducive to giving full play to the lithium-supplementing effect of the lithium-supplementing material and improving the first charging efficiency and overall electrochemical performance of the battery. In addition, the preparation process is simple and controllable, the production cost is low, and it is easy to industrialize.
[0015] The positive electrode material provided in the third aspect of the present application contains the lithium-supplementing composite material provided in the present application or contains the lithium-supplementing composite material prepared by the preparation method of the lithium-supplementing composite material provided in the present application. Therefore, the positive electrode material has good lithium-supplementing effect and structural stability.
[0016] The secondary battery provided in the fourth aspect of the present application contains the positive electrode material provided in the present application, and therefore, the electrochemical performance of the secondary battery can be improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0018] Figure 1 is a preparation process flow chart of a preparation method of a lithium-supplementing composite material provided in an embodiment of the present application;
[0019] Figure 2is a schematic structural diagram of the lithium-supplementing composite material provided in an embodiment of the present application;
[0020] Figure 3 is a schematic structural diagram of the lithium-supplementing composite material provided in an embodiment of the present application;
[0021] Among them, the reference numerals in the figure are:
[0022] 1-lithium replenishing material core, 2-coating layer, 21-hydrophobic region, 22-hydrophilic region. DETAILED DESCRIPTION
[0023] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.
[0024] In this application, the term "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural. The character " / " generally indicates that the associated objects are in an "or" relationship.
[0025] In this application, "at least one" means one or more, and "plurality" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c", can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.
[0026] It should be understood that in the various embodiments of the present application, the size of the serial numbers of the above-mentioned processes does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.
[0027] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "said" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.
[0028] The weight of the relevant components mentioned in the embodiment description of the present application can not only refer to the specific content of each component, but also represent the proportional relationship between the weights of the components. Therefore, as long as the content of the relevant components is proportionally enlarged or reduced according to the embodiment description of the present application, it is within the scope disclosed in the embodiment description of the present application. Specifically, the mass described in the embodiment description of the present application can be a mass unit known in the chemical industry such as μg, mg, g, kg, etc.
[0029] The terms "first" and "second" are used only for descriptive purposes to distinguish objects such as substances from each other, and should not be understood as indicating or implying relative importance or implicitly indicating the number of indicated technical features. For example, without departing from the scope of the embodiments of the present application, the first XX may also be referred to as the second XX, and similarly, the second XX may also be referred to as the first XX. Thus, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features.
[0030] In a first aspect, an embodiment of the present application provides a lithium-supplementing composite material, comprising a lithium-supplementing material and a coating layer coated on the surface of the lithium-supplementing material, wherein the coating layer contains an anionic surfactant.
[0031] The lithium-supplementing composite material provided in the embodiment of the present application comprises a lithium-supplementing material and a coating layer coated on the surface of the lithium-supplementing material, the coating layer contains an anionic surfactant, and the lithium-supplementing material contained therein can be used for lithium-supplementing. When the battery is in the first cycle of charging, the lithium-supplementing material can replenish the lithium ions consumed by the formation of the SEI film at the negative electrode, so that the lithium ions in the battery system remain abundant, thereby improving the battery's first charging efficiency and overall electrochemical performance. The anionic surfactant coating layer contained therein effectively prevents the generation of residual alkali, can reduce the residual alkali value of the lithium-supplementing material, can alleviate the damage of the residual alkali to the binder in the positive electrode slurry, and reduce the viscosity of the positive electrode slurry, thereby achieving uniform coating and improving the quality of the positive electrode sheet. In addition, the anionic surfactant is tightly attached to the surface of the lithium-supplementing material, which can increase the stability of the material structure, prevent the lithium-supplementing material from agglomerating, and is conducive to giving full play to the lithium-supplementing effect of the lithium-supplementing material, thereby further improving the battery's first charging efficiency and overall electrochemical performance.
[0032] In an embodiment, the hydrophobic groups contained in the anionic surfactant are at least partially bound to the surface of the lithium supplementing material, or the hydrophilic groups contained in the anionic surfactant are partially bound to the surface of the lithium supplementing material. The "at least" in the "the hydrophobic groups contained in the anionic surfactant are at least partially bound to the surface of the lithium supplementing material" can mean part or all. For example, Figure 2As shown, the hydrophobic groups (alkyl carbon chain ends) contained in the anionic surfactant are all bound to the surface of the lithium supplement material core 1. It can be understood that the hydrophobic groups contained in the anionic surfactant are all distributed on the surface of the lithium supplement material core 1 to form a hydrophobic area 21; the hydrophilic groups (sulfate ends (-MSO4) or sulfonate ends) contained in the anionic surfactant are all distributed on the surface of the hydrophobic area to form a hydrophilic area 22. The hydrophobic area 21 and the hydrophilic area 22 constitute the coating layer 2. The thickness of the hydrophobic area 21 is 0.5 to 350 nm, and the thickness of the hydrophilic area 22 is 1 to 150 nm. In practical applications, the thickness of the hydrophobic area 21 should be selected to be greater than the thickness of the hydrophilic area 22. This can improve the stability of the lithium supplement material structure, prevent erosion by the external environment, extend the service life of the lithium supplement material, and reduce storage costs. For another example, Figure 3 As shown, the hydrophobic groups contained in the anionic surfactant are partially bound to the surface of the lithium supplement material core 1, and the hydrophilic groups contained in the anionic surfactant are partially bound to the surface of the lithium supplement material core 1, which can refer to that most of the hydrophobic groups contained in the anionic surfactant are distributed on the surface of the lithium supplement material core 1, and a small part of the hydrophilic groups contained in the anionic surfactant are distributed on the surface of the lithium supplement material core 1, so that most of the hydrophobic groups and a small part of the hydrophilic groups distributed on the surface of the lithium supplement material can form a hydrophobic area 21, only a small part of the hydrophobic groups are distributed on the surface of the hydrophobic area 21, and most of the hydrophilic groups are distributed on the surface of the hydrophobic area 21, and the small part of the hydrophobic groups and most of the hydrophilic groups distributed on the surface of the hydrophobic area 21 form a hydrophilic area 22, and the hydrophobic area 21 and the hydrophilic area 22 together constitute the coating layer 2. The hydrophobic area 21 contained in the coating layer 2 provided in the present application is distributed on the surface of the lithium supplement material. On the one hand, it can protect the lithium supplement material, isolate the lithium supplement material from contact with the air, avoid corrosion of the lithium supplement material by water, oxygen and carbon dioxide in the air, and improve the stability of the lithium supplement material; on the other hand, it can effectively prevent the generation of residual alkali, reduce the residual alkali value of the lithium supplement material, alleviate the damage of the residual alkali to the binder in the positive electrode slurry, and reduce the viscosity of the positive electrode slurry, thereby achieving uniform coating and improving the quality of the positive electrode sheet.
[0033] In the embodiment, the content of the anionic surfactant accounts for 0.1-50% of the total mass of the lithium-supplementing composite material, for example, 0.1%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 20%, 30%, 40%, 50%. Within the content range of the anionic surfactant provided in this embodiment, it is beneficial for the anionic surfactant to be closely combined with the surface of the lithium-supplementing material, increase the stability of the material structure, effectively prevent the lithium-supplementing material from agglomerating, and optimize the lithium-supplementing effect of the lithium-supplementing material.
[0034] In an embodiment, the anionic surfactant includes at least one of an alkyl sulfonate anionic surfactant and an alkyl sulfate anionic surfactant. For example, the anionic surfactant is an alkyl sulfonate anionic surfactant, or the anionic surfactant is an alkyl sulfate anionic surfactant, or the anionic surfactant includes an alkyl sulfonate anionic surfactant and an alkyl sulfate anionic surfactant.
[0035] In an embodiment, the number of carbon atoms of the alkyl group in the alkyl sulfonate anionic surfactant is 10 to 20. The sulfonate in the alkyl sulfonate anionic surfactant includes at least one of an alkali metal sulfonate and an alkaline earth metal sulfonate. The alkali metal sulfonate is selected from at least one of sodium sulfonate, potassium sulfonate, rubidium sulfonate, cesium sulfonate and francium sulfonate. The alkaline earth metal sulfonate is selected from at least one of beryllium sulfonate, magnesium sulfonate, calcium sulfonate, strontium sulfonate and barium sulfonate. For example, the alkyl sulfonate anionic surfactant corresponding to the alkali metal sulfonate can be sodium dodecyl sulfonate, sodium undecyl sulfonate, sodium dodecyl sulfonate, sodium tridecyl sulfonate, sodium tetradecyl sulfonate, sodium hexadecyl sulfonate, sodium octadecyl sulfonate, potassium dodecyl sulfonate, potassium dodecyl sulfonate. The alkyl sulfonate anionic surfactant corresponding to the alkaline earth metal sulfonate can be magnesium dodecyl sulfonate and magnesium dodecyl sulfonate.
[0036] In an embodiment, the carbon number of the alkyl group in the alkyl sulfate anionic surfactant is 10 to 20. The sulfate in the alkyl sulfate anionic surfactant includes at least one of an alkali metal sulfate and an alkaline earth metal sulfate. The alkali metal sulfate is selected from at least one of sodium sulfate, potassium sulfate, rubidium sulfate, cesium sulfate and francium sulfate. The alkaline earth metal sulfate is independently selected from at least one of beryllium sulfate, magnesium sulfate, calcium sulfate, strontium sulfate and barium sulfate. For example, the alkyl sulfonate anionic surfactant corresponding to the alkali metal sulfonate can be sodium dodecyl sulfate, sodium undecyl sulfate, sodium dodecyl sulfate, sodium tridecyl sulfate, sodium tetradecyl sulfate, sodium hexadecyl sulfate, sodium octadecyl sulfate, potassium dodecyl sulfate, potassium dodecyl sulfate. The alkyl sulfonate anionic surfactant corresponding to the alkaline earth metal sulfonate can be magnesium dodecyl sulfate and magnesium dodecyl sulfate.
[0037] In an embodiment, the coating layer has a thickness of 1 nm to 5 μm, such as 1 nm, 5 nm, 10 nm, 20 nm, 40 nm, 60 nm, 80 nm, 100 nm, 200 nm, 300 nm, 400 nm, 600 nm, 800 nm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm. Within the thickness range of the coating layer provided in this embodiment, the particle size of the lithium-supplementing composite material can be adjusted, which is conducive to giving full play to the lithium-supplementing effect of the lithium-supplementing material and improving the stability of the material, thereby improving the first charge efficiency and overall electrochemical performance of the battery.
[0038] In an embodiment, the molecular formula of the lithium supplement material is Li x A y O z , wherein A includes at least one of Ni, Co, Fe, Cu, Mg, Mn, Cr, Zn, Ti, and Zr, 1<x<10, 0<y<4, 0<z<8, preferably 1<x<7, 1≤y<4, 1<z<5. In a specific embodiment, the molecular formula of the lithium supplement material can be but is not limited to Li2NiO2, Li2CuO2, Li6CoO4, Li5FeO4, Li5AlO4, Li6Co 0.5 Mn 0.5 O4、Li6 Ni 0.5 Co 0.5 O4. These lithium replenishing materials can be used to replenish lithium. When the battery is in the first cycle of charging, the lithium replenishing materials can replenish the lithium ions consumed by the formation of SEI film at the negative electrode, so that the lithium ions in the battery system remain abundant, thereby improving the battery's first charging efficiency and overall electrochemical performance.
[0039] In the embodiment, the morphology of the lithium supplement material can be controlled as needed, such as particles or other morphologies. The lithium supplement material is preferably in particle morphology, which can be primary particles or secondary particles. The particle size of the lithium supplement material satisfies: 0.1μm≤D50≤100μm, the particle size of the lithium supplement composite material satisfies: 0.1μm≤D50≤100μm, and the specific surface area of the composite material is 0.1 to 100m 2 / g. Within the range of the particle size of the lithium-supplementing material and the particle size and specific surface area of the composite material provided in the embodiments of the present application, it is beneficial to give full play to the lithium-supplementing effect of the lithium-supplementing material and improve the stability of the material, thereby improving the first charging efficiency and overall electrochemical performance of the battery. In a specific embodiment, the particle size of the lithium-supplementing material can be but is not limited to 0.1μm, 1μm, 2μm, 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 12μm, 14μm, 16μm, 18μm, 20μm, 22μm, 25μm, 50μm, 75μm, 100μm. The particle size of the lithium-supplemented composite material may be, but is not limited to, 0.1 μm, 1 μm, 3 μm, 5 μm, 7 μm, 9 μm, 11 μm, 13 μm, 15 μm, 17 μm, 19 μm, 21 μm, 23 μm, 25 μm, 27 μm, 29 μm, 30 μm, 60 μm, or 100 μm.
[0040] A second aspect of the present application provides a method for preparing a lithium-supplemented composite material, comprising the following steps:
[0041] S10: preparing a solution containing anionic surfactant;
[0042] S20: adding the lithium supplement material to a solution containing an anionic surfactant for mixing, and then drying to obtain a lithium supplement composite material.
[0043] The method for preparing the lithium-supplementing composite material provided in the embodiment of the present application comprises first preparing a solution containing an anionic surfactant; then adding the lithium-supplementing material to the solution containing the anionic surfactant for mixing, and then drying to obtain the lithium-supplementing composite material. The present application uses an anionic surfactant to coat the lithium-supplementing material, which is conducive to giving full play to the lithium-supplementing effect of the lithium-supplementing material and improving the first charging efficiency and overall electrochemical performance of the battery. In addition, the preparation process is simple and controllable, the production cost is low, and it is easy to industrialize.
[0044] In the above step S10, the method for preparing the solution containing anionic surfactant includes: adding the anionic surfactant into the solvent and dissolving it according to the mass ratio of the anionic surfactant to the solvent being 1:(0.1-3.5) to obtain the solution containing the anionic surfactant.
[0045] In an embodiment, the solvent may be selected from at least one of an aqueous solvent and an organic solvent. For example, the aqueous solvent may be selected from at least one of ammonia and water. The organic solvent may be selected from at least one of ethanol, methanol, ethylene glycol, butanol, isobutanol, NMP, and n-butanol.
[0046] In the above step S20, under an inert atmosphere, the lithium supplement material is added to a solution containing an anionic surfactant and mixed so that the solution containing the anionic surfactant is uniformly adsorbed on the surface of the lithium supplement material, and then a drying treatment is performed to completely volatilize the solvent in the solution containing the anionic surfactant, thereby obtaining a lithium supplement composite material in which the lithium supplement material is coated with the anionic surfactant.
[0047] In an embodiment, the drying step may include: stirring at a temperature of 40 to 130° C. for 1 to 5 hours, that is, stirring at a speed of 60 to 1200 rpm / min for 1 to 5 hours at a temperature of 40 to 130° C. to completely volatilize the solvent in the solution containing the anionic surfactant. If the drying step of this embodiment is adopted, the solvent used to dissolve the anionic surfactant may be selected from at least one of an aqueous solvent and an organic solvent.
[0048] In a specific embodiment, the solvent is water, and the anionic surfactant is added to water and dissolved according to the mass ratio of the anionic surfactant to water being 1: (0.1-3.5) to obtain a solution containing the anionic surfactant; the lithium supplement material is added to the solution containing the anionic surfactant for mixing, and then stirred at a temperature of 40-130° C. for 1-5 hours to completely volatilize the water in the solution containing the anionic surfactant, and the hydrophobic groups are all distributed on the surface of the lithium supplement material to form a hydrophobic area, and the hydrophilic groups are all distributed on the surface of the hydrophobic area to form a hydrophilic area, that is, the alkyl carbon chain end contained in the anionic surfactant is distributed on the surface of the lithium supplement material to form a hydrophobic area, and the sulfate end or sulfonate end is distributed on the surface of the hydrophobic area to form a hydrophilic area, to obtain a lithium supplement composite material.
[0049] In a specific embodiment, the solvent is a mixed solvent of water and ethanol, and the mass ratio of the anionic surfactant to the mixed solvent is 1: (0.1-3.5), and the anionic surfactant is added to the mixed solvent to dissolve to obtain a solution containing the anionic surfactant; after the lithium supplement material is added to the solution containing the anionic surfactant for mixing treatment, it is stirred at a temperature of 40-130° C. for 1-5 hours to completely volatilize the mixed solvent in the solution containing the anionic surfactant, and most of the hydrophobic groups are distributed on the surface of the lithium supplement material, and only a small part of the hydrophilic groups are distributed on the surface of the lithium supplement material, so that most of the hydrophobic groups and a small part of the hydrophilic groups distributed on the surface of the lithium supplement material form a hydrophobic area, only a small part of the hydrophobic groups are distributed on the surface of the hydrophobic area, and most of the hydrophilic groups are distributed on the surface of the hydrophobic area, so that a small part of the hydrophobic groups and most of the hydrophilic groups distributed on the surface of the hydrophobic area form a hydrophilic area, that is, most of the alkyl carbon chain ends in the anionic surfactant are distributed on the surface of the lithium supplement material, and only a small part of the sulfate or sulfonate ends are distributed on the surface of the lithium supplement material, to obtain a lithium supplement composite material.
[0050] In other embodiments, the drying step may further include: using a freeze dryer for drying. Specifically, the freeze dryer is used to freeze the solvent contained in the solution containing the anionic surfactant adsorbed on the surface of the lithium supplementing material into a solid state, and then the solvent therein is sublimated from the solid state into a gaseous state, thereby achieving the purpose of drying the solvent. If the method of drying the solvent using a freeze dryer in this embodiment is used, the solvent used to dissolve the anionic surfactant is an aqueous solvent, for example, water, ammonia water, or a mixture of water and ammonia water.
[0051] A third aspect of the embodiments of the present application provides a positive electrode material, which contains the lithium-supplementing composite material provided in the present application or the lithium-supplementing composite material prepared by the preparation method of the lithium-supplementing composite material provided in the present application.
[0052] The positive electrode material provided in the embodiments of the present application contains the lithium-supplementing composite material provided in the present application or contains the lithium-supplementing composite material prepared by the preparation method of the lithium-supplementing composite material provided in the present application. Therefore, the positive electrode material has good conductivity and structural stability.
[0053] A fourth aspect of an embodiment of the present application provides a secondary battery, which contains the positive electrode material provided by the present application.
[0054] The secondary battery provided in the embodiment of the present application contains the positive electrode material provided in the present application, and therefore, the electrochemical performance of the secondary battery can be improved.
[0055] The following describes the invention in conjunction with specific embodiments.
[0056] Example 1
[0057] This embodiment provides a lithium-supplementing composite material and a preparation method thereof. The lithium-supplementing composite material includes a lithium-supplementing material Li2Ni 0.5 Cu 0.5 O2 and coated on Li2Ni 0.5 Cu 0.5 The sodium dodecyl sulfate coating layer on the surface of O2; wherein the sodium dodecyl sulfate coating layer contains lithium ions distributed on the lithium supplement material Li2Ni 0.5 Cu 0.5 The dodecyl hydrophobic area on the O2 surface and the sodium sulfate-terminated hydrophilic area distributed on the surface of the dodecyl hydrophobic area.
[0058] The preparation method of the lithium-supplementing composite material of this embodiment comprises the following steps:
[0059] S10: according to the sodium dodecyl sulfate accounting for 0.1% of the total mass of the lithium-supplementing composite material, sodium dodecyl sulfate is weighed and dissolved in water to obtain a sodium dodecyl sulfate aqueous solution;
[0060] S20: Under nitrogen atmosphere, Li2Ni 0.5 Cu 0.5 The O2 lithium supplement material was added to the sodium dodecyl sulfate aqueous solution and mixed evenly, and then stirred at 40 ° C for 3 h to obtain sodium dodecyl sulfate coated Li2Ni 0.5 Cu 0.5 Lithium-replenishing composite materials of O2 lithium-replenishing materials.
[0061] After testing, Li2Ni 0.5 Cu 0.5 The particle size of the O2 core is 1.34 μm, the thickness of the sodium dodecyl sulfate coating layer is 15 nm, the thickness of the dodecyl hydrophobic region is 9 nm, the thickness of the sodium sulfate end hydrophilic region is 6 nm, the D50 particle size of the lithium-supplemented composite material is 1.35 μm, and the specific surface area of the lithium-supplemented composite material is 0.56 m 2 / g.
[0062] Example 2
[0063] This embodiment provides a lithium-supplementing composite material and a preparation method thereof. The lithium-supplementing composite material includes a lithium-supplementing material Li2Ni 0.5 Cu 0.5 O2 and coated on Li2Ni 0.5 Cu 0.5 The sodium dodecyl sulfate coating layer on the surface of O2; wherein the sodium dodecyl sulfate coating layer contains lithium ions distributed on the lithium supplement material Li2Ni 0.5 Cu 0.5 The dodecyl hydrophobic area on the O2 surface and the sodium sulfate-terminated hydrophilic area distributed on the surface of the dodecyl hydrophobic area.
[0064] The preparation method of the lithium-supplementing composite material of this embodiment comprises the following steps:
[0065] S10: according to the sodium dodecyl sulfate accounting for 1% of the total mass of the lithium-supplementing composite material, weighing sodium dodecyl sulfate and dissolving it in water to obtain a sodium dodecyl sulfate aqueous solution;
[0066] S20: Under nitrogen atmosphere, Li2Ni 0.5 Cu 0.5 The O2 lithium supplement material was added to the sodium dodecyl sulfate aqueous solution and mixed evenly, and then stirred at 40 ° C for 3 h to obtain sodium dodecyl sulfate coated Li2Ni 0.5 Cu 0.5 Composite materials of O2 lithium replenishing materials.
[0067] After testing, Li2Ni 0.5 Cu 0.5 The particle size of the O2 core is 1.34 μm, the thickness of the sodium dodecyl sulfate coating layer is 98 nm, the thickness of the dodecyl hydrophobic region is 78 nm, the thickness of the sodium sulfate end hydrophilic region is 20 nm, the D50 particle size of the lithium-supplemented composite material is 1.45 μm, and the specific surface area of the lithium-supplemented composite material is 0.56 m 2 / g.
[0068] Example 3
[0069] This embodiment provides a lithium-supplementing composite material and a preparation method thereof. The lithium-supplementing composite material includes a lithium-supplementing material Li2Ni 0.5 Cu 0.5 O2 and coated on Li2Ni 0.5 Cu 0.5 The sodium dodecyl sulfate coating layer on the surface of O2; wherein the sodium dodecyl sulfate coating layer contains lithium ions distributed on the lithium supplement material Li2Ni 0.5 Cu 0.5The dodecyl hydrophobic region on the O2 surface and the sodium sulfate-terminated hydrophilic region coated on the dodecyl hydrophobic region.
[0070] The preparation method of the lithium-supplementing composite material of this embodiment comprises the following steps:
[0071] S10: according to the sodium dodecyl sulfate accounting for 5% of the total mass of the lithium-supplementing composite material, weighing sodium dodecyl sulfate and dissolving it in water to obtain a sodium dodecyl sulfate aqueous solution;
[0072] S20: Under nitrogen atmosphere, Li2Ni 0.5 Cu 0.5 The O2 lithium supplement material was added to the sodium dodecyl sulfate aqueous solution and mixed evenly, and then stirred at 40 ° C for 3 h to obtain sodium dodecyl sulfate coated Li2Ni 0.5 Cu 0.5 Lithium-replenishing composite materials of O2 lithium-replenishing materials.
[0073] After testing, Li2Ni 0.5 Cu 0.5 The particle size of the O2 core is 1.34 μm, the thickness of the sodium dodecyl sulfate coating layer is 189 nm, the thickness of the dodecyl hydrophobic region is 140, the thickness of the sodium sulfate end hydrophilic region is 49 nm, the D50 particle size of the lithium-supplemented composite material is 1.51 μm, and the specific surface area of the lithium-supplemented composite material is 0.56 m 2 / g.
[0074] Example 4
[0075] This embodiment provides a lithium-supplementing composite material and a preparation method thereof. The lithium-supplementing composite material includes a lithium-supplementing material Li2Ni 0.5 Cu 0.5 O2 and coated on Li2Ni 0.5 Cu 0.5 The sodium dodecyl sulfate coating layer on the surface of O2; wherein the sodium dodecyl sulfate coating layer contains lithium ions distributed on the lithium supplement material Li2Ni 0.5 Cu 0.5 The dodecyl hydrophobic area on the O2 surface and the sodium sulfate-terminated hydrophilic area distributed on the surface of the dodecyl hydrophobic area.
[0076] The preparation method of the lithium-supplementing composite material of this embodiment comprises the following steps:
[0077] S10: according to the fact that the sodium dodecyl sulfate accounts for 10% of the total mass of the lithium-supplementing composite material, sodium dodecyl sulfate is weighed and dissolved in water to obtain a sodium dodecyl sulfate aqueous solution;
[0078] S20: Under nitrogen atmosphere, Li2Ni 0.5 Cu 0.5The O2 lithium supplement material was added to the sodium dodecyl sulfate aqueous solution and mixed evenly, and then stirred at 40 ° C for 3 h to obtain sodium dodecyl sulfate coated Li2Ni 0.5 Cu 0.5 Lithium-replenishing composite materials of O2 lithium-replenishing materials.
[0079] After testing, Li2Ni 0.5 Cu 0.5 The particle size of the O2 core is 1.34 μm, the thickness of the sodium dodecyl sulfate coating layer is 350 nm, the thickness of the dodecyl hydrophobic region is 230, the thickness of the sodium sulfate end hydrophilic region is 120 nm, the D50 particle size of the lithium-supplemented composite material is 1.69 μm, and the specific surface area of the lithium-supplemented composite material is 0.56 m 2 / g.
[0080] Example 5
[0081] This embodiment provides a lithium-supplementing composite material and a preparation method thereof. The lithium-supplementing composite material includes a lithium-supplementing material Li2Ni 0.5 Cu 0.5 O2 and coated on Li2Ni 0.5 Cu 0.5 The potassium dodecyl sulfonate coating layer on the surface of O2; wherein the potassium dodecyl sulfonate coating layer contains lithium ions distributed on the lithium supplement material Li2Ni 0.5 Cu 0.5 The dodecyl hydrophobic region on the O2 surface and the potassium sulfonate-terminated hydrophilic region distributed on the surface of the dodecyl hydrophobic region.
[0082] The preparation method of the lithium-supplementing composite material of this embodiment comprises the following steps:
[0083] S10: according to the fact that the potassium dodecyl sulfonate accounts for 5% of the total mass of the lithium-supplementing composite material, potassium dodecyl sulfonate is weighed and dissolved in water to obtain a potassium dodecyl sulfonate aqueous solution;
[0084] S20: Under nitrogen atmosphere, Li2Ni 0.5 Cu 0.5 The O2 lithium supplement material was added to the potassium dodecyl sulfonate aqueous solution and mixed evenly, and then stirred at 40 ° C for 3 h to obtain potassium dodecyl sulfonate coated Li2Ni 0.5 Cu 0.5 Lithium-replenishing composite materials of O2 lithium-replenishing materials.
[0085] After testing, Li2Ni 0.5 Cu 0.5 The particle size of the O2 core is 1.34 μm, the thickness of the potassium dodecyl sulfonate coating is 189 nm, the thickness of the dodecyl hydrophobic region is 134 nm, the thickness of the potassium sulfonate hydrophilic region is 55 nm, the D50 particle size of the lithium-supplemented composite material is 1.51 μm, and the specific surface area of the lithium-supplemented composite material is 0.56 m2 / g.
[0086] Example 6
[0087] This embodiment provides a lithium-supplementing composite material and a preparation method thereof. The lithium-supplementing composite material includes a lithium-supplementing material Li6Co 0.5 Mn 0.5 O4 and coated on Li6Co 0.5 Mn 0.5 The sodium dodecyl sulfate coating layer on the surface of O4; wherein the sodium dodecyl sulfate coating layer contains lithium-supplementing material Li2Ni 0.5 Cu 0.5 The dodecyl hydrophobic region on the O2 surface and the sodium sulfonate end hydrophilic region distributed on the surface of the dodecyl hydrophobic region.
[0088] The preparation method of the lithium-supplementing composite material of this embodiment comprises the following steps:
[0089] S10: according to the sodium dodecyl sulfate accounting for 5% of the total mass of the lithium-supplementing composite material, weighing sodium dodecyl sulfate and dissolving it in water to obtain a sodium dodecyl sulfate aqueous solution;
[0090] S20: Under nitrogen atmosphere, Li6Co 0.5 Mn 0.5 The O4 lithium supplement material was added to the sodium dodecyl sulfate aqueous solution and mixed evenly, and then stirred at 40 ° C for 3 h to obtain sodium dodecyl sulfate coated Li6Co 0.5 Mn 0.5 O4 lithium-replenishing material lithium-replenishing composite material.
[0091] After testing, Li6Co 0.5 Mn 0.5 The particle size of the O4 core is 1.34 μm, the thickness of the sodium dodecyl sulfate coating layer is 180 nm, the thickness of the dodecyl hydrophobic region is 136 nm, the thickness of the sodium sulfonate end hydrophilic region is 44 nm, the D50 particle size of the lithium-supplemented composite material is 1.47 μm, and the specific surface area of the lithium-supplemented composite material is 0.55 m 2 / g.
[0092] Comparative Example 1 This comparative example provides a lithium supplement material Li2Ni 0.5 Cu 0.5 O2, without anionic surfactant coating.
[0093] Comparative Example 2
[0094] This comparative example provides a lithium supplement material Li6Co 0.5 Mn 0.5 O4, without anionic surfactant coating.
[0095] Related performance test analysis:
[0096] 1. Lithium-ion battery assembly:
[0097] The lithium-supplement composite materials provided in the above-mentioned Examples 1 to 6 and the lithium-supplement materials provided in Comparative Examples 1 to 2 are respectively assembled into positive electrodes and lithium-ion batteries according to the following methods:
[0098] The lithium-supplementing composite materials provided in Examples 1 to 6 and the lithium-supplementing materials provided in Comparative Examples 1 to 2 were respectively mixed with LiFePO4 positive electrode materials in a mass ratio of 95:5 to obtain a mixture, and then the mixture, polyvinylidene fluoride, and SP-Li were mixed and ball-milled in a mass ratio of 95:3:2 to obtain a positive electrode slurry, and the positive electrode slurry was coated on the surface of an aluminum foil, rolled, and vacuum dried at a temperature of 110° C. overnight to obtain a positive electrode sheet;
[0099] Negative electrode: lithium metal sheet; diaphragm: polypropylene microporous separator;
[0100] Electrolyte: Ethylene carbonate and ethyl methyl carbonate were mixed in a volume ratio of 3:7, and LiPF6 was added to form an electrolyte, the concentration of LiPF6 was 1 mol / L;
[0101] Lithium-ion battery assembly: Lithium-ion batteries are assembled in an inert atmosphere glove box according to the structure of lithium metal sheet-diaphragm-electrolyte-positive electrode sheet.
[0102] 2. Lithium-ion battery electrochemical performance test analysis:
[0103] The batteries containing the positive electrode sheets of the lithium-supplementing composite materials provided in Examples 1 to 6 are respectively recorded as Examples S1 to S6, and the batteries containing the lithium-supplementing materials in Comparative Examples 1 to 2 are respectively recorded as Comparative Examples DS1 to DS2. The first charge and discharge test was performed at 0.066C, with a test voltage of 2.5V-4.3V, and then a 200-cycle test was performed at 2C, with a test voltage of 2.5V-3.75V. The battery electrochemical performance test results are shown in Table 1 below:
[0104] Table 1
[0105]
[0106] It can be seen from Table 1 that the first charge and discharge gram-specific capacity and capacity retention rate of Examples S1 to S5 are significantly higher than those of Comparative Examples DS1 to DS2. The first charge gram-specific capacity can be as high as 177.5 mAh / g, while the first charge gram-specific capacity in Comparative Examples DS1 and DS2 can only reach a maximum of 163.3 mAh / g. This indicates that the use of anionic surfactants to coat lithium-supplementing materials in the present application can reduce the residual alkalinity value on the surface of the lithium-supplementing materials and improve their structural stability. When used in combination with positive electrode materials, their lithium-supplementing performance can be more fully exerted.
[0107] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.
Claims
1. A lithium supplement composite material, characterized in that: It comprises a lithium supplement material and a coating layer coated on the surface of the lithium supplement material, wherein the coating layer contains an anionic surfactant; The hydrophobic group contained in the anionic surfactant is at least partially bound to the surface of the lithium supplementing material, or the hydrophilic group contained in the anionic surfactant is partially bound to the surface of the lithium supplementing material; The hydrophobic group and the hydrophilic group contained in the anionic surfactant form a hydrophobic region and a hydrophilic region on the surface of the lithium supplement material, and the hydrophobic region and the hydrophilic region constitute the coating layer; the molecular formula of the lithium supplement material is Li x A y O z , wherein A includes at least one of Ni, Co, Fe, Cu, Mg, Mn, Cr, Zn, Ti, and Zr, 1<x<10, 0<y<4, 0<z<8.
2. The lithium-supplementing composite material according to claim 1, characterized in that: The content of the anionic surfactant accounts for 0.1-50% of the total mass of the lithium-supplementing composite material.
3. The lithium-supplementing composite material according to claim 1, characterized in that: The anionic surfactant includes at least one of an alkyl sulfonate anionic surfactant and an alkyl sulfate anionic surfactant.
4. The lithium-supplementing composite material according to claim 3, characterized in that: The sulfonate in the alkyl sulfonate anionic surfactant comprises at least one of an alkali metal sulfonate and an alkaline earth metal sulfonate; and / or The sulfate in the alkyl sulfate anionic surfactant comprises at least one of an alkali metal sulfate and an alkaline earth metal sulfate; and / or The carbon number of the alkyl group in the alkyl sulfonate anionic surfactant is 10 to 20; and / or The carbon number of the alkyl group in the alkyl sulfate anionic surfactant is 10 to 20.
5. The lithium-supplementing composite material according to claim 4, characterized in that: The alkali metal sulfonate is selected from at least one of sodium sulfonate, potassium sulfonate, rubidium sulfonate, cesium sulfonate and francium sulfonate; and / or The alkaline earth metal sulfonate is at least one selected from beryllium sulfonate, magnesium sulfonate, calcium sulfonate, strontium sulfonate and barium sulfonate; and / or The alkali metal sulfate is selected from at least one of sodium sulfate, potassium sulfate, rubidium sulfate, cesium sulfate and francium sulfate; and / or The alkaline earth metal sulfate is selected from at least one of beryllium sulfate, magnesium sulfate, calcium sulfate, strontium sulfate and barium sulfate.
6. The lithium-supplementing composite material according to any one of claims 1 to 5, characterized in that: The particle size of the lithium supplement material satisfies: 0.1 μm ≤ D50 ≤ 100 μm; and / or The coating layer has a thickness of 1 nm to 5 μm; and / or The particle size of the lithium-supplementing composite material satisfies: 0.1 μm ≤ D50 ≤ 100 μm; and / or The specific surface area of the lithium-supplementing composite material is 0.1 to 100 m 2 / g.
7. A method for preparing the lithium-supplementing composite material according to any one of claims 1 to 5, characterized in that: The following steps are involved: preparing a solution containing an anionic surfactant; The lithium supplement material is added into the solution containing anionic surfactant for mixing, and then dried to obtain the lithium supplement composite material.
8. The method for preparing the lithium-supplementing composite material according to claim 7, characterized in that: The drying step comprises: stirring at a temperature of 40-130° C. for 1-5 hours; or The step of drying comprises: using a freeze dryer for drying.
9. A positive electrode material, characterized in that: The positive electrode material contains the lithium-supplement composite material according to any one of claims 1 to 6 or the lithium-supplement composite material prepared by the preparation method of the lithium-supplement composite material according to any one of claims 7 to 8.
10. A secondary battery, characterized in that: The secondary battery contains the positive electrode material according to claim 9.
Citation Information
Patent Citations
Polar-solvent-resistant lithium supplement additive and preparation method thereof
CN112751033A